Characterization of initial ankle-foot prosthesis prescription patterns in U.S. Service members following unilateral transtibial amputation - Patrick G. Monaghan; Ashley D. Knight; Ashley D. Knight; Ashley D. Knight; Sarah A. Brinkerhoff; Kenneth D. Harrison; Christopher L. Dearth; Christopher L. Dearth; Brad D. Hendershot; Brad D. Hendershot; Brad D. Hendershot; JoEllen M. Sefton; et al. (Frontiers Media S.A., 2023)
IntroductionThe purpose of this study was to explore relationships between patient-specific characteristics and initial ankle-foot prosthesis prescription patterns among U.S. Service members with unilateral transtibial limb loss.MethodsA retrospective review of health records identified 174 individuals with unilateral transtibial limb loss who received care at Walter Reed National Military Medical Center between 2001 and 2019. We examined patient-specific factors such as demographics, participant duty status at injury and amputation, amputation etiology, and timing between injury, amputation, and initial prescription. The type of first prescribed ankle-foot prosthesis was categorized as energy storing and return - nonarticulating, energy storing and return - articulating, or computer controlled.ResultsSex, amputation etiology, time from injury to initial prescription, and time from amputation to initial prescription differed by type of initial ankle-foot prosthesis prescription. Service members with shorter intervals between injury-initial prescription and amputation-initial prescription, and those injured by combat blast, were more likely to receive a non-articulating device. Incorporating sex, time from injury-initial prescription, time from amputation-initial prescription, and amputation etiology as predictors of prosthesis type, we were able to correctly classify 72% of all first prostheses prescribed.DiscussionPatient-specific characteristics such as sex, the time between injury-initial prescription, time from amputation-initial prescription and amputation etiology are essential characteristics that influence initial ankle-foot prosthesis prescription patterns in U.S. Service members.